2019
DOI: 10.1016/j.physbeh.2019.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Potential moderators of the portion size effect

Abstract: Aim: The robust effect of portion size on intake has led to growing interest in why individuals consume more food when served larger portions. A number of explanations have been proposed, and this review aims to provide insight into potential underlying factors by summarizing recent studies testing moderators of the portion size effect. Summary of findings: Provision of portion size information, such as through labeling or training in portion control, failed to attenuate food intake in response to increasing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 69 publications
(111 reference statements)
0
29
0
2
Order By: Relevance
“…Thus, changes to portion sizes in the environment have potential downstream consequences beyond a single eating occasion [7,8]. However, relatively little is known about the mechanism responsible for this effect [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, changes to portion sizes in the environment have potential downstream consequences beyond a single eating occasion [7,8]. However, relatively little is known about the mechanism responsible for this effect [9].…”
Section: Introductionmentioning
confidence: 99%
“…Portion size has been identified as a potential contributor to the overconsumption of high energy density (HED) foods (Zuraikat et al . ). Laboratory based, systematic studies with adults have demonstrated that providing large portions of energy dense foods promotes greater energy intake relative to small portions (Rolls et al .…”
Section: Introductionmentioning
confidence: 97%
“…Food environments presenting consumers with large sizes of highly liked, HED foods may encourage overconsumption (Zuraikat et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Young children consume larger quantities of food in the presence of larger food portion sizes, which may be attributable to social norms, visual cues, or changes in the microstructure of eating [1]. This is known as the portion size effect (PSE).…”
Section: Introductionmentioning
confidence: 99%